2012
DOI: 10.1016/j.ijrobp.2012.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Prone Accelerated Partial Breast Irradiation After Breast-Conserving Surgery: Five-year Results of 100 Patients

Abstract: Purpose To report the 5-year results of a prospective trial of three-dimensional conformal external beam radiotherapy (3D-CRT) to deliver accelerated partial breast irradiation in the prone position (P-APBI). Methods Post-menopausal patients with Stage I breast cancer with non palpable <2 cm tumors, negative margins, and negative nodes, positive hormonal receptors, and no extensive intraductal component (EIC) were eligible. The trial was offered only once eligible patients had refused to undergo standard who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 21 publications
2
51
0
Order By: Relevance
“…29,36,37 However, other clinical series of APBI delivered with 3D-CRT or IMRT reported acceptable cosmetic outcomes. 9,[38][39][40][41][42][43][44][45] These conflicting studies raise the hypothesis that subtle variations in planning techniques and/or dose constraints may substantially modify the therapeutic ratio of EBRT-based APBI. [46][47][48] In light of ongoing research, particularly the National Surgical Adjuvant Breast and Bowel Project B-39/RTOG 0413 trial, 5 which has yet to report cosmetic outcomes for patients treated with 3D-CRT APBI, the task force opted not to make a specific recommendation either for or against the use of EBRT-based APBI at this time.…”
Section: Comment On External Beam Apbimentioning
confidence: 99%
“…29,36,37 However, other clinical series of APBI delivered with 3D-CRT or IMRT reported acceptable cosmetic outcomes. 9,[38][39][40][41][42][43][44][45] These conflicting studies raise the hypothesis that subtle variations in planning techniques and/or dose constraints may substantially modify the therapeutic ratio of EBRT-based APBI. [46][47][48] In light of ongoing research, particularly the National Surgical Adjuvant Breast and Bowel Project B-39/RTOG 0413 trial, 5 which has yet to report cosmetic outcomes for patients treated with 3D-CRT APBI, the task force opted not to make a specific recommendation either for or against the use of EBRT-based APBI at this time.…”
Section: Comment On External Beam Apbimentioning
confidence: 99%
“…To overcome the integral dose problem large variety of techniques using multiple directions with non-coplanar beams exist as well [17][18][19][20]. To date only the NYU group treated large cohort of PBI patients with mini-tangents [7]. However they use seroma based target volume definition and reduced CTV-PTV margin that required by the supine RTOG trial 0413 [21].…”
Section: Discussionmentioning
confidence: 99%
“…PBI offers decreased overall treatment time and reduced dose delivery to uninvolved portion of the breast and adjacent organs at risk [3][4][5][6]. PBI has been already introduced in prone (Pr) position [7,8]. Formenti et al have reported comparable 5-year efficacy, cosmetics, and toxicity of prone three-dimensional conformal external beam radiation therapy to other forms of PBI [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Combined with MRI and/or CT to assess tumor extent, GammaPod has the potential to accurately deliver high radiation dose to the gross tumor and its micro extensions. Breathing motion should have little effect on the geometrical accuracy because the patient is treated in prone position 10 and the skin of the breast is immobilized by the vacuum-assisted breast cup.…”
Section: Discussionmentioning
confidence: 99%